Maastrichtian ammonites from the Biscay region (France, Spain) - Ward, P; Kennedy, W (1993)
Maastrichtian sediments exposed in the Bay of Biscay region at coastal sections at Zumaya and Sopelana, northern Spain, and Hendaye and Bidart, France, yield the most diverse Upper Maastrichtian ammonite faunas yet recovered. Thirty-two species/subspecies referred to 21 genera are described, one of which, Anapachydiscus terminus is new. The ranges of all taxa are fully documented and provide the basis for a four-fold division of the uppermost Campanian and Maastrichtian, with zones of Pseudokossmaticeras tercense (oldest), Pachydiscus (P.) epiplectus, Anapachydiscus fresvillensis, and A. terminus (youngest). This represents the most refined, and first properly documented, ammonite zonation for the Maastrichtian of western Europe, and can be directly correlated with the belemnite zonation developed for the white chalks of northern Europe. The extinction of the last ammonites, documented here, occurred at relatively high standing diversity and appears to have been sudden and catastrophic. -Authors